Induction Chemotherapy With FOLFIRINOX Followed by Chemoradiation With Gemcitabine in Patients With Borderline-Resectable Pancreatic Ductal Adenocarcinoma. (8th October 2022) - Acuna-Villaorduna, Ana; Shankar, Viswanathan; Wysota, Michael; Jirgal, Amanda; Kabarriti, Rafi; Bellemare, Sarah; Goldman, Inessa; Kaubisch, Andreas; Aparo, Santiago; Goel, Sanjay; Chuy, Jennifer
Introduction: Perioperative therapy is standard for patients with borderline-resectable pancreatic ductal adenocarcinoma (BR-PDAC); however, an optimal neoadjuvant regimen is lacking. We assessed the efficacy of FOLFIRINOX chemotherapy followed by gemcitabine-based chemoradiation as preoperative therapy. Methods: Patients received 4 cycles of FOLFIRINOX, followed by 6-weekly gemcitabine with concomitant intensity-modulated radiation. The primary endpoint was the R0 resection rate. Secondary outcomes included resection rate, overall-response, overall survival (OS), progression-free survival (PFS), and tolerability. The trial was terminated early due to slow accrual. A Simon's optimal two-stage phase II trial single arm design was used. The primary hypothesis of treatment efficacy was tested using a multistage group sequential inference procedure. The secondary failure time analysis endpoints were assessed using the Kaplan-Meier procedure and the Cox regression model. Results: A total of 22 patients enrolled in the study, 18 (81.8%) completed neoadjuvant treatment. The bias corrected R0 rate was 55.6% (90% CI: 33.3, 68.3; P value = .16) among patients that received at least 1 cycle of FOLFIRINOX and was 80% among patients that underwent surgery. The median OS was 35.1 months. The median PFS among patients that underwent surgery was 34 months. Conclusion: An R0 resection rate of 55.6% is favorable. Neoadjuvant FOLFIRINOX followed by concomitant Gemcitabine with radiation was well-tolerated. NCT01897454 Graphical Abstract